Surface and thin film analysis : a compendium of principles, instrumentation, and applications - Friedbacher, Gernot (Wiley-VCH, 2011)
Surveying and comparing all techniques relevant for practical applications in surface and thin film analysis, this second edition of a bestseller is a vital guide to this hot topic in nano- and surface technology. This new book has been revised and updated and is divided into four parts - electron, ion, and photon detection, as well as scanning probe microscopy. New chapters have been added to cover such techniques as SNOM, FIM, atom probe (AP),and sum frequency generation (SFG). Appendices with a summary and comparison of techniques and a list of equipment suppliers make this book a rapid reference for materials scientists, analytical chemists, and those working in the biotechnological industry.